Macht-(W)Orte: kulturelle Geographien des Rechts und der Ökonomie am Beispiel südasiatischer Migrationsgeschichten - Schwegmann, Raphael (Sozial- und Kulturgeographie, 2018)
Law and the economy in space and time: Taking South Asian migration biographies as examples, Raphael Schwegmann traces the globalizing mobilization of power from a post-colonial perspective.